Exploring the ontological dimension of dialogic education through an evaluation of the impact of Internet mediated dialogue across cultural difference. (March 2019) - Wegerif, Rupert; Doney, Jonathan; Richards, Andrew; Mansour, Nasser; Larkin, Shirley; Jamison, Ian
Abstract: It has been claimed that dialogic education implies a direction of change upon an ontological dimension from monologic closed identities in the direction of more dialogic identifications characterised by greater openness to the other and greater identification with the process of dialogue. This paper recapitulates that theory and then provides an empirical illustration of what it looks like in practice. In order to do this a methodology for researching the impact of dialogic education is outlined and applied to the evaluation of the impact of a programme designed to promote greater dialogic open-mindedness: the Tony Blair Institute for Global Change's Generation Global Project (GG) supports schools in over twenty different countries to engage in dialogue with each other through videos and blogs. The methodology put forward argues that the understanding sought by educational research is dialogic in that it emerges from the dialogue between inside and outside perspectives. The findings offer some clear evidence of a shift in identifications resulting from dialogue through the analysis of changes in online language use supported by interview evidence. This study suggests that a pedagogical intervention can produce identity change in the direction of becoming more dialogic and shows that it is possible to evaluate this change.